Variable structure control of switched systems based on Lyapunov-Metzler-SPR systems - Cardim, Rodrigo [UNESP]; Teixeira, Marcelo C.M. [UNESP]; Assunção, Edvaldo [UNESP]; Covacic, Márcio R. (Institute of Electrical and Electronics Engineers (IEEE), 2008)
This paper presents two Variable Structure Controllers (VSC) for continuous-time switched plants. It is assumed that the state vector is available for feedback. The proposed control system provides a switching rule and also the variable structure control input. The design is based on Lyapunov-Metzler (LM) inequalities and also on Strictly Positive Real (SPR) systems stability results. The definition of Lyapunov-Metzler-SPR (LMS) systems and its direct application in the design of VSC for switched systems are introduced in this paper. Two examples illustrate the design of the proposed VSC, considering a plant given by a switched system with a switched-state control law and two linear time-invariant systems, that are not controllable and also can not be stabilized with state feedback. ©2008 IEEE.
Keywords: Control systems; Control theory; DC motors; Feedback; Invariance; Spatial variables control; Spectrum analyzers; State feedback; Surface plasmon resonance; Switching systems; Telecommunication networks; Time varying control systems; Variable structure control; A-Plant; Continuous-time; Linear-time-invariant systems; Lyapunov; Stability results; State vectors; Strictly positive real; Switched systems; Switched-state control; Switching rules; Variable structure controllers; Variable structure systems; System stability